Medicine-related problems: A recurrent issue among residents living in nursing homes - Dorj, Gereltuya; Lim, Renly; Ellett, Lisa Kalisch; Kelly, Thu-Lan; Andrade, Andre; Widagdo, Imaina; Pratt, Nicole; Bilton, Rebecca; Roughead, Elizabeth (Frontiers in Pharmacology, 2022)
Aim: To examine the incidence and nature of medicine-related problems over time experienced by nursing home residents. Method: We analysed records collected in the Reducing Medicine-Induced Deterioration and Adverse Events (ReMInDAR) trial. The trial pharmacists provided services to reduce medicine induced deterioration and adverse reactions for residents every 8-weeks over a year. The problems identified by the pharmacists were documented in reports and subsequently classified independently by research pharmacists using the D.O.C.U.M.E.N.T system. The number and type of problems at each service and time to develop a new problem post first session were assessed. All analyses were performed using R software (Version 4.1.1). Results: The cohort was 115 nursing home residents who received 575 services. In the 12-months, a total of 673 medicine-related problems or symptom reports were identified in 112 residents. Most residents (75%) experienced a new medicine-related problem by the fourth month post the first assessment. After the first session, the proportion of residents with a new medicine-related problem or symptom report declined at each repeated pharmacy session (59% at visit 2 vs 28% at visit 6, p<0.01). Conclusion: Residents living in nursing homes frequently experience medication-related problems. Our results suggest clinical pharmacist services performed every 4-months may have the potential to reduce the medicine-related problems in nursing homes.